Cocaine-Induced Acute Pancreatitis. Issue 12 (4th December 2020) - Strzepka, Jessica; Tian, Frances; Nassani, Najib; Garcia-Bedoya, Olga; Yazici, Cemal
ABSTRACT: Cocaine use is prevalent worldwide and affects multiple organ systems. Ischemia of the esophagus and small bowel are examples of its gastrointestinal complications. Cocaine-induced pancreatitis is a rare entity. Only 8 cases of cocaine-induced pancreatitis have been described in the literature. We present a rare case of a 61-year-old man cocaine user who presented with his first episode of acute pancreatitis (AP) in which common etiologies of AP were excluded. In addition, we explore the pathophysiology of cocaine-induced AP.